THINKING ALOUD PROTOCOL FOR SMART TRANSLATION - Fikriani Aminun Omolu; Andi Mappewali (Premise: Journal of English Education and Applied Linguistics, 2020)
A language is an important tool in communication. To produce a smooth relationship between countries that have different languages, the English language functions as Lingua Franca. To understand the information in English, a good understanding is needed. Being able to translate English texts is one of the basic forms of understanding itself. Unfortunately, numerous English language learners; from junior high schools to university levels, are still experiencing problems in this translation. This study aims to uncover the strategies of students in translating English texts into Indonesian by using the Thinking Aloud Protocol method. The subjects of this study were students in semester V (five) who had gone through Structure I to Structure IV subjects. This research was conducted in the scope of the University of Muhammadiyah Palu. From this research, the most widely used translation strategy is done by students as well as the prototype of the translation process to produce good translations